Technical Standardization as a Barrier to International Trade: Basic Conceptual Clarifications for Understanding the Issue - Román Díaz, Miguel (2011)
This article has some basic concepts related to the technical normalization. It is necessary to understand this notion and so that it can be an obstacle to the international trade. The technical barriers are located by the doctrine within the denominated nontariff barriers.